METODE DAKWAH ORANG TUA SUKU BANJAR MENDIDIK ANAK-ANAK PATUHI AJARAN ISLAM - Ismail, Abdul Munir; Aula, Rashidatul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Islamic teachings require parents to educate children by using appropriate and memorable methods. This paper examines the da'wah methods of Banjare parents to educate children so that they adhere to the teachings of Islam. The purpose of this research is to investigate the practice of Islamic values of Banjare parents in raising their children to obey the teachings of Islam perfectly. This research uses quantitative survey methods. Survey forms are distributed to 160 at Sekolah Menengah Pertama (Junior High School). Data were analyzed using the SPSS application method for Windows (Version 23). The results found that parents of Banjare tribes told their children to pray five times a day, train children to fast, read the Koran, respect parents and teachers, guard the limits of genitalia, keep halal food and non-halal food, control emotional stability, design emotional periods, front of the child, guiding the child's behaviour and having the children dress modestly. The implication of this research shows that parents from the Banjare tribe are seen teaching their children to obey God, educating children so that children are of good morality and obedient to Islamic law.Keywords: Da'wah Method, Parents, Education Child, and Obedience to Islamic Teachings.